La région de Québec : peuplement et problèmes de population - Grenier, Fernand (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1962)
The region of Québec comprises nine counties and at the time of the 1961 census had a total population of 643,843 inhabitants. The author briefly describes the physical characteristics of the region and shows that its unity resides in the dominating influence of Québec, regional capital. In the study of the settlement, the author's analysis is devoted particularly to a criticism of the « rang » System of rural settlement. The growth of the population is rather appreciable even though all of the counties except Québec experience a net migration loss. The pattern of urban influence seems unbalanced. The Québec agglomeration alone includes more than half of the population of the region. Aside from Québec, the region has only small towns with population smaller than 5,000. In order to retain its importance, the region needs to undergo development in all sectors of its economy, particularly in that of secondary industry, which is currently somewhat retarded.